A striking new species of Harpalyce (Leguminosae, Brongniartieae) from highland cerrado of Bahia, Brazil - São-Mateus, Wallace Messias Barbosa; Cardoso, Domingos Benício Oliveira Silva; Queiroz, Luciano Paganucci De; Jardim, Jomar Gomes (Phytotaxa, 2016)
Harpalyce magnibracteata is described and illustrated as a new species of the tribe Brongniartieae (Papilionoideae, Leguminosae). It is chiefly diagnosed by the unique combination of persistently attached, large leaf-like amplexicaul bracts measuring 1.2‒2.3 × 1.2‒2.3 cm, features that do not match with any other species of the genus. The new species grows as a small shrub in upland patches of savanna vegetation on gravelly soils of the mountains of Chapada Diamantina.